Quel financement pour les jeunes entreprises technologiques bruxelloises - Nicolas Pary; Olivier Witmeur (Brussels Studies, 2019)
New technology-based firms are sometimes faced with financing difficulties and are able to count on various schemes and public aid to help them in their start-up phase. In this article, through case studies, we examine the ways in which entrepreneurs in Brussels have obtained financing and, in particular, their use of public schemes. We end with the description of an efficient system in which, nevertheless, the numerous grants are sometimes diverted from their objective. Based on these results and a focus group with stakeholders in the field, we discuss recommendations by insisting on the importance of a revision of grants in order to limit deadweight effects, a refinancing of investment structures and public loans, and better general coordination of these schemes.